Design, preparation and characterisation of myoglobin artificial metalloproteins for applications in catalysis - Venckutė, Evelina (The University of Edinburgh, 2025)
To date, artificial metalloprotein (ArM) toolbox has offered novel means for improving the green chemistry metrics of many synthetic processes. These include but are not limited to the highly selective synthesis of bioactive molecules (e.g. pharmaceuticals), recycling of chemical waste and degradation of environmental pollutants, sustainable energy conversion (e.g. H2 evolution) as well as biosensing of small molecules for applications in human healthcare. In this work, heme-free myoglobin (Mb) variant was substituted with synthetic redox active porphyrin (PPIX) and salophen cofactors (Schiff base) bearing first-row transition metal centres (Fe, Mn, Co and Cu) to give access to a new ArM library. Structural characterisation, including non-covalent cofactor binding in the latter biohybrid catalysts, was performed using native nanoESI-MS and CD, FTIR, UV-vis, EPR spectroscopy methods. Notably, although salophen-bound Mbs demonstrated lower reconstitution efficiency compared to the porphyrin-bound counterparts, they could still attain a native-like protein fold and displayed an improved thermal stability relative to the heme-free Mb (Tm = 65-69 °C vs 61 °C). It was also showed that their binding could be further improved by using rationally engineered Mb scaffolds. Moreover, protein immobilisation on the pyrolytic graphite and glassy carbon working electrodes using hydrophobic polymer films allowed to probe intrinsic to the metal centre differences in the Mb ArM redox behaviour. Cyclic voltammetry (CV) analysis revealed > 0.64 V negatively shifted redox potential for the Co(II)/(Co(I) redox couple in the Co porphyrin-bound Mb relative to the heme reduction potential in the native Mb. In addition, CV analysis of the Mn porphyrin-bound Mb systems revealed unusual twostate redox pathway which was likely not governed by the axial H2O ligation. Unlike in the native Mb, this electron transfer process was almost pH independent and, hence, unique to the Mn porphyrin-bound Mbs. Both 1st and 2nd coordination sphere mutants of the native Mb and its ArMs were effective in further tuning their redox properties. Lastly, this study examined the redox potentials of Fe and Co salophen bound Mbs using direct electrochemical methods for the first time. Preliminary screening of their catalytic properties revealed improved activity in small molecule (e.g. H2O2) activation reactions relative to that of the synthetic cofactor counterparts alone. Overall, this study has demonstrated that cofactor substitution is a powerful strategy for preparing redox active ArMs with distinctive electronic properties and non-native catalytic functions. This work has set a foundation for further catalysis studies using synthetic porphyrin and salophen cofactor-bound Mbs.
Keywords: Artificial Metalloproteins (ArM); Myoglobin (Mb); Catalysis; Redox; Cofactor